Studies on the Photoelectrocatalysis Induced Degradation of Pharmaceutical Drug using Fabricated TiO2 Electrode - Singla, Jaishnu (My University, 2015)
Photoelectrocatalytic degradation of Ornidazole using Ti/TiO2 photoanode and copper as cathode was investigated in the present study. The degradation rate was observed to follow first-order kinetics. Anodic oxidation technique was used for the fabrication of TiO2 electrode for the degradation of Ornidazole. The crystal structure, morphology, bandgap energy and flatband potential characterized by X-Ray diffraction, scanning electron microscopy, UV-Vis spectroscopy and electrochemical impendence spectroscopy, respectively. The performance of photoelectrocatalysis was evaluated in terms of %degradation along with operating parameters such as pH, initial concentration and degradation time. Optimization was done by using BBD under response surface methodology. Under optimum conditions the actual %degradation and COD removal during photoelectrocatalytic degradation of Ornidazole by the proposed Ti/TiO2 electrode were 95.34% and 75% respectively. The predictions agree well with the experimental results. Through comparison among PEC, EC and PC, it was found that photoelectrocatalytic oxidation was convenient and effective way to treat and mineralize the pharmaceutical compound present in wastewater.
M.Tech. (Environmental Science and Technology)
Keywords: Photoelectrocatalysis; Pharma-drug; TiO2; Electrode; Degradation; Energy and Environmental Science; Energy; SEE